2012
DOI: 10.1126/scitranslmed.3003421
|View full text |Cite
|
Sign up to set email alerts
|

A Peptide Derived from Endostatin Ameliorates Organ Fibrosis

Abstract: Fibroproliferative disorders such as idiopathic pulmonary fibrosis and systemic sclerosis have no effective therapies and result in significant morbidity and mortality due to progressive organ fibrosis. We examined the effect of peptides derived from endostatin on existing fibrosis and fibrosis triggered by two potent mediators, transforming growth factor–β (TGF-β) and bleomycin, in human and mouse tissues in vitro, ex vivo, and in vivo. We identified one peptide, E4, with potent antifibrotic activity. E4 prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
123
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(129 citation statements)
references
References 36 publications
6
123
0
Order By: Relevance
“…Our previous study confirmed that systemic application of endostatin could prevent hypertrophic scar formation in the rabbit ear model (Ren et al, 2013). Yamaguchi et al (2012) found that endostatin-derived peptide ameliorates organ fibrosis that is triggered by transforming growth factor-β (TGF-β) and bleomycin in human and mouse tissues. However, the molecular mechanisms by which endostatin mediates fibrosis in fibroblasts remain poorly understood.…”
Section: Introductionsupporting
confidence: 71%
“…Our previous study confirmed that systemic application of endostatin could prevent hypertrophic scar formation in the rabbit ear model (Ren et al, 2013). Yamaguchi et al (2012) found that endostatin-derived peptide ameliorates organ fibrosis that is triggered by transforming growth factor-β (TGF-β) and bleomycin in human and mouse tissues. However, the molecular mechanisms by which endostatin mediates fibrosis in fibroblasts remain poorly understood.…”
Section: Introductionsupporting
confidence: 71%
“…Increased concentrations of lysyl oxidase (LOX), an amine oxidase critical for the initiation of collagen and elastin crosslinking (32), and increased mRNA concentrations of collagen Types I and III have also been reported in murine models of lung fibrosis (33). In this report, MK2i treatment markedly reduced TGF-b-induced fibronectin and collagen expression.…”
Section: Discussionmentioning
confidence: 53%
“…This may at first seem counterintuitive as proteins up-regulated in disease tend to serve a pathologic role. However, the scientific literature catalogues a growing number of proteins up-regulated in disease that work to counter the disease process, reestablish homeostasis, and return the body to its original state of health (61)(62)(63), and we have found that FAP behaves in such a fashion in pulmonary fibrosis. This study is the first to demonstrate that the absence of FAP worsens the development of pulmonary fibrosis after lung injury, establishing a protective role for FAP in the lung.…”
Section: Discussionmentioning
confidence: 94%
“…Previous work by others has shown significant biological activity of peptides generated from proteolytic degradation of collagens, for example the chemotactic properties of the matrikine, PGP, or the antifibrotic actions of endostatin, a product of proteolytic degradation of collagen XVIII (61,74,75). Indeed, we did identify increased neutrophilic inflammation in BAL fluid from FAP-null mice compared with wild type in our bleomycin model as well as a more prominent inflammatory infiltrate overall in the BAL from FAP-null mice versus wild type after thoracic FIGURE 11.…”
Section: Discussionmentioning
confidence: 99%